PENGARUH GINI RASIO, PENGELUARAN NON MAKANAN DAN BELANJA MODAL TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Nina, Gek Ayu; Rustariyuni, Surya Dewi (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Economic development in Indonesia is essentially building a whole person, so that it can improve people's welfare. Community welfare is one of the goals of the SDGs and is a reflection of the success of development carried out by the government, measured using the Human Development Index (HDI). Bali's HDI as a whole continues to increase, but the difference in HDI figures that is quite far between the districts / cities in Bali is an important problem to overcome. This difference shows that there is an inequality between regions. The research objectives to be achieved are: 1) to analyze the influence of the ratio gini, non-food expenditure per capita, and capital expenditure on poverty in the regency / city of Bali Province; 2) To analyze the influence of the ratio gini, non-food expenditure per capita capital expenditure and poverty on the welfare of the people in the regency / city of Bali Province; and 3) To analyze the influence of the ratio gini, non-food expenditure per capita and capital expenditure through poverty on the welfare of the people in the regency / city of Bali Province. The analysis technique uses path analysis and the results of Gini ratio research and capital expenditure have no effect on the number of poor people while non-food expenditure has a positive and significant effect. The results of testing the Gini Ratio variable on public welfare, this ratio, non-food expenditure and the number of poor people have a positive and significant effect on the welfare of society while capital expenditure has no influence.Keyword : gini ratio, HDI, number of poor people, capital expenditureJEL Classification:E65, H76